PRODUKSI BAHAN ORGANIK, PROTEIN KASAR DANBAHAN EKSTRAK TANPA NITROGEN HIJAUAN PASTURA ALAM YANG DIINTRODUKSI JENIS RUMPUT DAN LEGUM YANG BERBEDA - Bernadete Barek Koten; R. Naisoko; R. Wea; A. Semang; Thomas Lapenangga (Partner, 2018)
The aim of the study was to evaluate the production of organic matter, crude protein, nitrogen  free extract of  natural pasture forages which was introduced by different types of grasses and legumes which had been carried out on natural pastures in Tuatuka Sub-District, East Kupang District for 7 months from April to October 2017, based on randomized block design (RBD) with 5 treatments and 4 groups, namely: P0: Natural pasture without introduction, CP: natural pastura introduced by  Cynodon plectotachyus, DA: natural pastura introduced by Dichantium aristatum, DV: natural pastura introduced by Desmanthus virgatus, and C: natural pastura introduced by Clitoria ternatea. The variables observed were organic matter (OM) production, crude protein (CP) production, nitrogen  free extract (NFE) production of forages. Data were analyzed for variance based on RBD and continued with Duncan Test. Variance analysis shows that OM production, CP production and NFE production of natural pasture forages  are strongly influenced (P <0.01) by species introduction. Duncan's test showed that introduction with C, DV and CP produced OM, CP,and NFE production  of forage higher and different (P <0.05) with DA and P0. Average of OM, CP, and NFE  production of forage are: 2.38 tons / ha, 0.10 tons / ha and 1.18 tons / ha. It was concluded that the introduction of natural pastura with superior species was able to increase the production of OM, CP, and NFE forages and species of  Clitoria ternatea, Desmanthus virgatus and Cynodon plectotachyus producing the highest forage production.